Modulation of La Crosse Virus Infection in Aedes albopictus Mosquitoes Following Larval Exposure to Coffee Extracts - Eastep, Nicole E.; Albert, Rachel E.; Anderson, Justin R. (Frontiers in Physiology, 2012)
The mosquito-borne La Crosse virus (LACV; Family Bunyaviridae) may cause encephalitis, primarily in children, and is distributed throughout much of the eastern United States. No antivirals or vaccines are available for LACV, or most other mosquito-borne viruses, and prevention generally relies on mosquito control. We sought to determine whether coffee extracts could interfere with LACV replication and vector mosquito development. Both regular and decaffeinated coffee demonstrated significant reductions in LACV replication in direct antiviral assays. This activity was not due to the presence of caffeine, which did not inhibit the virus life cycle. Aedes albopictus (Skuse; Diptera: Culicidae) mosquito larvae suffered near total mortality when reared in high concentrations of regular and decaffeinated coffee and in caffeine. Following larval exposure to sublethal coffee concentrations, adult A. albopictus mosquitoes had significantly reduced whole-body LACV titers 5 days post-infection, compared to larvae reared in distilled water. These results suggest that it may be possible to both control mosquito populations and alter the vector competence of mosquitoes for arthropod-borne viruses by introducing antiviral compounds into the larval habitat.